Optimizing performance outcomes of manufacturing firms: Does plural sourcing matter? - Abdullah, Haim Hilman; Azim, Md Shamimul (Academy for Global Business Advancement (AGBA), 2015)
A prime question that has dominated much of strategic management research is: What determines superior firm performance? Over almost two decades, scholars have sought to examine the role of various factors that could possibly influence business performance of a firm.This is because regardless of the country‘s boundary consumers from other parts of the world, in fact, have financially benefited from continuous escalation on volume of products of lower prices imported from developing countries.The increased pressures from fickle consumers and uncertain business environment are making more and more firms to recognize the strategic role in the rapid change of business environment.The firms ought to have the capability of responding the changing business environment efficiently and effectively, where sourcing can play a significant role in order to achieve sustainable competitive advantage (Bruce & Daly, 2011; Gligor & Holcomb, 2014; MacCarthy & Jayarathne, 2012).Firms in the manufacturing sectors are facing the most inevitable challenge to decide whether products to make through internal effort, or solicit from outside independent suppliers (buy) with a high degree of economies-of-scale to enhance efficiency and productivity (Espino-Rodríguez & Lai, 2014; Hilman & Mohamed, 2011; Lafontaine & Slade, 2007). Efficiency and productivity thru reducing costs, maintain high quality, flexibility, improved delivery dependability, and prompt quick response enable a manufacturing firm to achieve competitiveness and performance (Su & Gargeya, 2012).These perspectives assessment to decide in-house production (Make) by adapting the cost strategy or source externally (buy) by adapting differentiation.There are fewer studies to understand the long-term benefits of outsourcing to the firms (Hunter & Hall, 2011; Premuroso, 2008). Previous researches have conceptualized sourcing strategy and its effects on organizational performance, in which some of them emphasize on make or buy of sourcing (Espino-Rodríguez et al., 2014; Hilman & Mohamed, 2011; Lamminmaki, 2011).Extent literature considered sourcing as an evident governance modes or forms but little attention has been given to the underlying quality of relationship of sourcing firms which might influence performance. Extent literature to date about the relationship quality focused mainly on western culture and stable business environment and yet little know about the manufacturer‘s relationships with its key suppliers in emerging economies (Yang, Yu, Liu, & Rui, 2015). Thus this study aims to provide an integrated model of competitive strategy, sourcing strategy, sourcing relationship quality and firm performance.Thus, the corresponding objective of this study is to address the quotation on how manufacturing firm can achieve better performance